The Implementation of English Teacher's Differentiated Instruction to Disabled Student in an Inclusive School - Aprilia Purnama Sari; Dewa Ayu Eka Agustini; Luh Diah Surya Adnyani (Indonesian Journal of Disability Studies, 2020)
Disabled student learns based on 2013 curriculum in an inclusive school. This student learns the same material with regular students. To help disabled student understands the material, the teacher should use an appropriate teaching strategy. Differentiated instruction is a teaching strategy of providing different options for students. It has 4 terms namely content, process, product, and learning environment. This study aimed at investigating the implementation of English teacher's differentiated instruction to disabled student in an inclusive school. This study was a qualitative research which employs a case study research design. The study was conducted in MM2 (Multi Media) class at SMKN 3 Singaraja as an inclusive school. The subject was an English teacher who already attended some workshops to teach disabled student. The data were gathered by observation and interview. The results showed that the English teacher differentiated the topics of the text, examples, sources, and the ways of explaining and reviewing the material in term of content. The teacher also gave pre-assessment to determine the topic for students' video. In term of process, the teacher sometimes differentiated the choices and instructions for disabled student and regular students. The teacher did not differentiate the product made by disabled student and regular students but sometimes differentiated the challenge, the topic, and the criteria. In term of learning environment, the teacher usually provided enough space, arranged the seatmate and seat for disabled student than regular students. She gave different rules or instructions depending on where the learning took place.